International Comparison of Surgical Management Practices for Necrotizing Enterocolitis in Neonates: Insights from Cohorts in the Netherlands and Finland - Lahr, Bineta E.; van Varsseveld, Otis C.; Klerk, Daphne H.; Pakarinen, Mikko; Koivusalo, Antti; Hulscher, Jan B.F. (European Journal of Pediatric Surgery, 2025)
Surgical management of necrotizing enterocolitis (NEC) can result in significant morbidity and mortality. Surgical management varies in the absence of international evidence-based guidelines. We aimed to gain insight into practice variation between expert centers in the Netherlands and Finland.Bicentric retrospective cohort study including all infants treated surgically for NEC (Bell's stage ≥IIA) in two centers in the Netherlands and Finland between 2000 and 2021. Main outcomes were preoperative, intraoperative, and 3-month postoperative characteristics.We included 191 patients (122 Dutch and 69 Finnish). Median gestational age and birth weight were lower in Finnish patients (median [min.–max.]: 25 + 4/7 [23 + 0/7–39 + 0/7] vs. 28 + 2/7 [23 + 6/7–41 + 6/7], p < 0.001, and 795 g [545–4,000] vs. 1,103 g [420–3,065], p < 0.001). Indication for surgery was mostly pneumoperitoneum in Finnish patients (56.5% vs. 37.7%; p = 0.02) versus clinical deterioration on conservative treatment in Dutch patients (51.6% vs. 23.2%; p < 0.001). A fixed-bowel loop was also more often an indication in Finland (20.3% vs. 3.3%; p < 0.001. Ostomy creation was more common in Finnish patients (92.8% vs. 53.3%; p < 0.001) and primary anastomosis in Dutch patients (29.5% vs. 4.4%; p < 0.001). Open-close procedures occurred in 13.9% of Dutch cases, versus 1.4% of Finnish cases (p = 0.004). Mortality at 3 months was comparable when excluding open-close procedures (24.8% vs. 19.1%; p = 0.46).We observed varying populations, indications for surgery, and surgical approaches in NEC between the Netherlands and Finland. The occurrence of open-close procedures is 10-fold higher (13.9% vs. 1.4%) in the Netherlands compared to Finland. Long-term outcomes remain to be studied. These results point toward significant practice variation and strengthen the need for European management guidelines.
Keywords: preterm infants; necrotizing enterocolitis; surgery; practice variations; neonatology